The influence of linguistic and cognitive factors on the time course of verb-based implicit causality. Issue 3 (March 2016) - Koornneef, Arnout; Dotlačil, Jakub; van den Broek, Paul; Sanders, Ted
In three eye-tracking experiments the influence of the Dutch causal connective "want" ( because ) and the working memory capacity of readers on the usage of verb-based implicit causality was examined. Experiments 1 and 2 showed that although a causal connective is not required to activate implicit causality information during reading, effects of implicit causality surfaced more rapidly and were more pronounced when a connective was present in the discourse than when it was absent. In addition, Experiment 3 revealed that—in contrast to previous claims—the activation of implicit causality is not a resource-consuming mental operation. Moreover, readers with higher and lower working memory capacities behaved differently in a dual-task situation. Higher span readers were more likely to use implicit causality when they had all their working memory resources at their disposal. Lower span readers showed the opposite pattern as they were more likely to use the implicit causality cue in the case of an additional working memory load. The results emphasize that both linguistic and cognitive factors mediate the impact of implicit causality on text comprehension. The implications of these results are discussed in terms of the ongoing controversies in the literature—that is, the focusing-integration debate and the debates on the source of implicit causality.